The Impact of Electricity Energy Production, Fossil Energy Consumption, Renewable Energy Consumption, Deforestation, and Agriculture towards Climate Change in Middle-Income Countries - Sasana, Hadi; Prasetyanto, Panji Kusuma; Wijayanti , Diah Lufti; Fatimah , Ari Nurul (International Journal of Energy Economics and Policy, 2023)
This study aims to determine the effect of electrical energy production, fossil energy consumption, renewable energy consumption, deforestation and agriculture on climate change in middle-income countries. The method of analysis uses the Fixed Effect Model Cross-section weight regression model. The results of the study found that the production of electrical energy, the consumption of fossil energy had a significant positive effect on climate change. The development of environmentally friendly technologies in the agricultural sector needs to be carried out so that the sector does not damage the climate in middle-income countries. Reducing deforestation and consumption of renewable energy in middle-income countries has a positive effect on efforts to cure climate change.